Design of a Groutless Clear Coffee Machine Using Distillation Method - Adi Pratama Putra; Wardhana, Megandhi Gusti; Hadi, Charis Fathul (Logic : Jurnal Rancang Bangun dan Teknologi, 2024)
Coffee is a plantation commodity that is made into a drink as one of the products that is popular with the public. Many coffee drink innovations have been made, one of which is a clear coffee drink without dregs. The process of making clear coffee can be done by the distillation method, namely the process of condensing the steam produced by a mixture of coffee powder and water. This study aims to obtain the design results of a clear coffee machine without dregs using the distillation method. The design is carried out based on the results of a patented study on making clear coffee. The coffee machine is made with a heating tube for a mixture of ground coffee and water, a steam collector tube and a distillation tube. The design results obtained a heating tube with a diameter of 25 cm and a height of 27 cm for a process capacity of 13.25 liters. Heating is performed using an LPG-fueled heater. The distillation process is carried out by cooling the water using a 15 watt aerator pump. The trial was carried out by processing 500 grams of fine coffee powder mixed with 2000 ml of water. The trial results obtained 500 ml of clear coffee with an average process time of ± 25 minutes.